Why do knees after total knee arthroplasty fail in different parts of the world? - Mathis, Dominic T. (J Orthop, 2020)
OBJECTIVE: The aim of this narrative review was to provide an overview of failure modes after total knee arthroplasty in different parts of the world based on data from worldwide representative studies and National Joint Registries. METHODS: A review of the available literature was performed using the keyword terms “total knee arthroplasty”, “revision”, “failure”, “reasons”, “causes”, “complications”, “epidemiology”, “etiology”; “assessment”, “painful knee”, “registry” and “national” in several combinations. The following databases were assessed: Pubmed (https://pubmed.ncbi.nlm.nih.gov), Cochrane Reviews (https://www.cochrane.org), Google Scholar (https://scholar.google.com). In addition, registry data were obtained directly from national registry archives. Due to the heterogeneity of available data it was decided to present the review in a narrative manner. RESULTS: Current literature report that infection has become the primary acute cause of TKA failure, while aseptic loosening and instability remain the overall most frequent reasons for revisions. Based on national registries certain tendencies can be deducted. The predominant overall failure mode of aseptic loosening is particularly found in Japan, United Kingdom, New Zealand and Switzerland. Leading early TKA failure mode represents infection with percentages of 20–30% in Sweden, Australia, New Zealand, Japan and the United States. Higher numbers could only be found in clinical studies on the Asian continent such as Korea (38%), China (53%), Iran (44%) and India (87%). CONCLUSION: Although there are regional differences in TKA failure modes, TKA fails worldwide especially due to infections and aseptic loosening. It is important to diagnose these in good time and reliably using appropriate, standardized diagnostics in order to recommend the best possible therapy to the patient.